TECHNOLOGY EXPERIMENTAL IMPLEMENTATION OF INTERCULTURAL EDUCATION OF STUDENTS BY MUSIC ACTIVITIES - Zheyuan, Wei (The Modern Higher Education Review, 2018)
The article presents the results of experimental work on introducing the technology of intercultural education of students by music in non-auditing work of a higher educational institution and assessing its effectiveness. It was shown that at the end of the forming stage of the experiment there was a significant decrease in the low level of formation of intercultural education of students in the experimental group and the growth of the indicator of a high level in comparison with the control.